1993
DOI: 10.2134/jeq1993.00472425002200040013x
|View full text |Cite
|
Sign up to set email alerts
|

Storage and Migration of Fallout Strontium‐90 and Cesium‐137 for Over 40 Years in the Surface Soil of Nagasaki

Abstract: The vertical migration of 90Sr and 117Cs produced by the explosion of the atomic bomb in 1945 was investigated in an unsaturated soil layer in the Nishiyama area of Nagasaki. The in situ migration rates of 90Sr and 137Cs were estimated to be 4.2 mm yr−1 and 1.0 mm yr−1, respectively, when the rate of movement of soil water was 2500 mm yr−1. The in situ Kd values of 90Sr and 137Cs were calculated to be 0.3 m3 kg−1 and 1.2 m3 kg−1, respectively. These are probably the only results that exist for the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…The estimated 137 Cs migration rate for the Nishiyama loam soil, which was obtained in situ at Nishiyama (Nagasaki), is 1.0 mm y 1 [13]. This is considerably less than the rainwater infiltration rate of 2.5 m y 1 .…”
Section: Resultsmentioning
confidence: 83%
“…The estimated 137 Cs migration rate for the Nishiyama loam soil, which was obtained in situ at Nishiyama (Nagasaki), is 1.0 mm y 1 [13]. This is considerably less than the rainwater infiltration rate of 2.5 m y 1 .…”
Section: Resultsmentioning
confidence: 83%
“…Like calcium, strontium has moderate mobility in soils and sediments, and sorbs moderately to metal oxides and clays (Hayes and Traina 1998 90 Sr determined in soil cores taken from the fallout area of the 1945 blast in Nagasaki, Japan were 496 and 300 L/kg, respectively (Mahara 1993). Migration rates for 90 Sr in soils from this area were estimated to be 4.2 mm/year when the percolation rate of soil water was 2,500 mm/year.…”
Section: Transport and Partitioningmentioning
confidence: 99%
“…Information about the partitioning and mobility of 90 Sr in environment is available (Bunde et al 1997(Bunde et al , 1998DOE 1996d;Kashparov et al 2001;Mahara 1993;Sokolik et al 2001;Toran 1994).…”
Section: Potential For Human Exposurementioning
confidence: 99%
“…Thus, it can be assumed that Cs and Sr are strongly retained in the top layer of organic soil [6]. For example, 40 years after the atomic bomb explosion in Nagasaki, Japan, Cs monitoring showed that 95% of the fallout was still present in the uppermost 10 cm of local soil [7] Manuscript received June 21, 2015; revised August 5, 2015. This work was partially supported by the -Human Security Engineering Education Program,‖ Graduate School of Engineering, Kyoto University.…”
Section: Introductionmentioning
confidence: 99%